A combined heuristic approach to nonlinear fixed-charge capacitated network design problem - Yoo, Woo-Sik; Kim, Jae-Gon; Kim, Chongman (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
The nonlinear fixed-charge capacitated network design problem (NFCNDP) is notoriously difficult and there is limited literature addressing this problem although the (linear) fixed-charge capacitated network design problem has been extensively studied. In this article, we propose a new heuristic approach to the NFCNDP. We develop a two-phase heuristic algorithm in which a constructive method is used to obtain an initial solution and the solution is iteratively improved using an improvement method. To overcome the myopia of the heuristic algorithm, we combine it with simulated annealing. Computational experiments are performed on benchmark test sets with convex and concave cost functions. Test results show that the suggested algorithm performs much better than commercial optimization solvers.